Breastfeeding and transmission of cytomegalovirus to preterm infants. Case report and kinetic of CMV-DNA in breast milk - Rossi Marta J; Castronari Roberto; Cenci Elio; Sensini Alessandra; Bragetti Patrizia; Chiavarini Manuela; Fantauzzi Ambra; Minelli Liliana (BMC, 2011)
Abstract Background Breastfeeding has a major impact on CMV epidemiology. Postnatal CMV reactivation's incidence during lactation is nearby the maternal seroprevalence. Although perinatal CMV infection has practically no consequences in term newborn, it may cause, in some cases, a severe symptomatic disease in preterm newborns. The aims of the present study are to evaluate the rate and clinical expression of CMV infection breast milk transmitted in preterm infants and to check the safety of the freezing treated breast milk. Methods The study included fifty-seven preterm infants and their CMV seropositive mothers. Fresh breast milk samples have been collected from 1st to 9th postpartum week. Both fresh breast milk and 72, 96, 120 hours frozen samples have been examined, checking the presence of CMV; urine samples have been tested too. Results 70.2% of tested mothers showed reactivation of the infection, and CMV-positive breast milk during the six weeks postpartum has been found. However, only one infant was infected by CMV, developing hepatic affection concomitantly with a multi-system involvement, as shown CMV DNA detection in urine, saliva, blood, gastric aspirate, and stools. Conclusion Freezing breast milk at -20°C and pasteurization may respectively reduce or eliminate the viral load.